Fractal Phototherapy in Neuroprotection of Glaucoma - M. V. Zueva; M. A. Kovalevskaya; O. V. Donkareva; A. I. Karankevich; I. V. Tsapenko; A. A. Taranov; V. B. Antonyan (Oftalʹmologiâ)
Purpose: to study the effect of low-intensity fractal light stimulation on the sensitivity in the visual field in patients with suspected glaucoma (SG) and primary open-angle glaucoma (POAG). Material and Methods. The study involved 146 people, including 98 patients of the main group (No. 1) and 49 people from the control group “placebo”-therapy (No. 2). Standard automatic perimetry was performed (SITA-Standard, Humphrey, CarlZeissMeditec, 24-2). The dynamics of the perimetry indices MD and PSD were evaluated before and after the course of a ten 10-minute session of fractal phototherapy or after a 10-day course of relaxation consisting in watching a particular training video twice a day. The maximum brightness of the flashes on the cornea during phototherapy was 10–12 lux, the fractal dimension of the optical signal was D = 1.4. Results. A two-week course of low-intensity stimulation with fractal optical signals reliably improved the MD reflected the common defect in the visual field, in all patients with SG and POAG. The expositions to videos with a relaxation program did not have a statistically significant effect on MD and PSD indices. The pronounced effect of fractal stimulation revealed in eyes with POAG III (a reduction of MD on average by 4.39 dB) suggests that even in advanced stages of glaucoma in the general population of retinal ganglion cells there is a significant percentage of cells that are still at the plastic stage of reversible functional changes and can respond positively to therapy. The results substantiate the feasibility of application neuroprotective therapy to patients with any stage of glaucoma, including the advanced stage. Conclusion. In this study, we first used the technology of fractal optical stimulation for the treatment of glaucoma. The first evidence of the neuroprotective effect of fractal phototherapy for POAG at different stages has been obtained. Fractal stimulation can be considered as a new non-pharmacological (physiotherapeutic) approach to neuroprotective therapy, whose potential and mechanisms need to be studied in future studies.